2020
DOI: 10.1161/atvbaha.119.313470
|View full text |Cite
|
Sign up to set email alerts
|

Taking One Step Back in Familial Hypercholesterolemia

Abstract: Objective: STAP1 , encoding for STAP1 (signal transducing adaptor family member 1), has been reported as a candidate gene associated with familial hypercholesterolemia. Unlike established familial hypercholesterolemia genes, expression of STAP1 is absent in liver but mainly observed in immune cells. In this study, we set out to validate STAP1 as a familial hypercholesterolemia gene. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 50 publications
0
13
2
1
Order By: Relevance
“…Furthermore STAP1 was suggested to be associated with FH, however, we were not able to confirm this in a recent study on 75 hypercholesterolemic patients from Berlin, Germany, who were negative for mutations in canonical FH genes 14,15 . In a recent study on mouse models and samples from STAP1 carriers the gene was ruled out as a FH causing candidate 16 . In 2010, a meta‐analysis of genome‐wide association studies identified multiple common single nucleotide polymorphisms (SNPs) to be strongly associated with elevated LDL‐C concentrations 17 .…”
Section: Introductioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Furthermore STAP1 was suggested to be associated with FH, however, we were not able to confirm this in a recent study on 75 hypercholesterolemic patients from Berlin, Germany, who were negative for mutations in canonical FH genes 14,15 . In a recent study on mouse models and samples from STAP1 carriers the gene was ruled out as a FH causing candidate 16 . In 2010, a meta‐analysis of genome‐wide association studies identified multiple common single nucleotide polymorphisms (SNPs) to be strongly associated with elevated LDL‐C concentrations 17 .…”
Section: Introductioncontrasting
confidence: 69%
“…14,15 In a recent study on mouse models and samples from STAP1 carriers the gene was ruled out as a FH causing candidate. 16 In 2010, a meta-analysis of genomewide association studies identified multiple common single nucleotide polymorphisms (SNPs) to be strongly associated with elevated LDL-C concentrations. 17 Talmud et al hypothesized that the mutation negative FH patients might carry a greater-than-average number of these common LDL-C raising variants and assembled a 12-SNP polygenic score based on the variants with the strongest LDL-C associations.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with ACMG criteria, clinically relevant variants were classified as pathogenic (class I), likely pathogenic (class II), and variants of unknown significance (class III). Since STAP1 is very unlikely to be a causative FH gene, variants in this gene were not considered [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…5 We excluded STAP1 variants from this analysis, as this is no longer considered a FH gene. 16,17 Next, the allele frequency of variants in the minor FH genes in FH mutation-negative patients was numerically compared with the allele frequency reported in the European non-Finnish population in gnomAD V2.1.1. (https:// gnomad.broadinstitute.org/).…”
Section: Dna Sequencingmentioning
confidence: 99%